Laser Processing of Low Optical Reflection Micro/Nano-patterned Si Substrates for SERS. (16th May 2017) - Verma, Ashwani Kumar; Das, Rupali; Soni, R.K.
ABSTRACT: Light collection efficiency and specific molecular detection are crucial factors for the performance of bio-chemical molecule sensors. In this paper, the low optical-reflection silicon (Si) substrates which combine reduced optical reflectivity by light trapping effect and high Raman enhancement ability of gold nanoparticles (Au-NPs) coated textured Si substrates are investigated for surface-enhanced Raman scattering (SERS). A fast, single-step and highly controllable nanosecond (ns) laser processing technique is employed to fabricate textured Si substrates under ambient conditions. Parallel arrays of micro-pyramids are fabricated on Si surface by direct laser writing two-dimensional structures. SEM micrographs clearly show well-ordered surface features in the form of micro-pyramid shape with well-defined sharp tips on the laser processed Si substrates. The aggregation of Si micro/nanoparticles on Si surface forms nanocavities and nanogaps and further enhances the surface roughness in order to minimize the optical reflection. The low optical reflection Si substrates exhibit optical reflection below 15% over a broad wavelength range from 300 nm to 1200 nm. The textured Si substrates with high signal reproducibility are successfully applied as SERS substrates to detect a very small concentration of Rhodamine B molecules with an average enhancement factor of the order of ∼10 7 . The low optical reflection and SERS signal amplification are also altered by the variation of laser pulse energy resulting into low optical reflection and high SERS signal intensity over the entire laser-patterned area. The effect of surface roughness on water contact angle was studied after the modification with Polydimethylsiloxane (PDMS), the surfaces show perfect superhydrophobicity with almost no water adhesion. This approach provides a novel high-speed and cost-effective method for fabricating SERS substrate with micro/nano-scale surfaces roughness and low optical reflection for high Raman signal enhancement.